The impact of NGOs on heritage objects and spaces - Dominika Hołuj (Ochrona Dziedzictwa Kulturowego, 2024)
In the context of an increasing social interest in cultural heritage and, consequently, a wide range of increasingly diversified grassroots activities related to the protection of heritage objects and spaces, there is a growing need for identifying the dimensions of social impact on cultural resources. The analysis of this issue in this article is based on the case of a group of public benefit organizations which are engaged in protecting heritage objects and spaces. As a result, the article identifies a group of factors which represent organizations’ impact in this area, giving attention to the perspective of target heritage objects and spaces, their surroundings and social and economic environment, public authorities and institutions, indirect beneficiaries, as well as considering the criterion of the time of impact (immediate, deferred and potential effects). The analysis is based on desk research, including a literature review, expert analyses, and with regard to empirical studies – reports prepared by public benefit organizations, the content of their websites and social media.